Experimental Archaeology in the Scottish Highlands - Susan Kruse (EXARC, 2019)
Over the past year, Archaeology for Communities in the Highlands (ARCH) has been running a series of experimental archaeology workshops in the Scottish Highlands. ARCH is a non-profit educational charity, providing learning opportunities inside and out for all ages, always with an eye on the legacy of the event. Our experimental archaeology project was a good example of this approach involving a wide range of the public while investigating research questions. We wanted a series of events to build a following and interest, showing a range of craft and technology from earliest settlers to modern times, using objects or structures found in the Highlands.